2022
DOI: 10.1001/jamanetworkopen.2022.0120
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 3 Paclitaxel-Based Chemoradiotherapy Regimens for Patients With Locally Advanced Esophageal Squamous Cell Cancer

Abstract: IMPORTANCE Multiple paclitaxel-based regimens are widely used in chemoradiation therapy against esophageal cancer, including regimens combining paclitaxel with fluorouracil, cisplatin, and carboplatin. However, which among these 3 regimens provides the best prognosis with minimum adverse events is still unknown. OBJECTIVE To compare the efficacy and adverse events of fluorouracil, cisplatin, and carboplatin in definitive chemoradiotherapy in patients with esophageal squamous cell carcinoma (ESCC). DESIGN, SETT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 12 publications
1
40
0
Order By: Relevance
“…In terms of safety, the most common grade 3-4 acute adverse events were neutropenia (58.3%) and leukopenia (56.5%). The incidence was higher than that of some previous studies [11,12], but similar to that reported by Tang et al [10].and highly consistent with the results of a 3-group, multi-center, randomized phase III clinical trial (ESO-Shanghai2) led by Fudan University Affiliated Cancer Hospital [23]. High hematological toxicity not only requires the optimization of the combination regimen and the dose of chemotherapeutic drugs, but also poses a challenge to improve the performance of chemotherapeutic drugs themselves.…”
Section: Discussionsupporting
confidence: 90%
“…In terms of safety, the most common grade 3-4 acute adverse events were neutropenia (58.3%) and leukopenia (56.5%). The incidence was higher than that of some previous studies [11,12], but similar to that reported by Tang et al [10].and highly consistent with the results of a 3-group, multi-center, randomized phase III clinical trial (ESO-Shanghai2) led by Fudan University Affiliated Cancer Hospital [23]. High hematological toxicity not only requires the optimization of the combination regimen and the dose of chemotherapeutic drugs, but also poses a challenge to improve the performance of chemotherapeutic drugs themselves.…”
Section: Discussionsupporting
confidence: 90%
“…Although the superiority of the TP regimen has been previously reported [11,24,25], a recent RCT has shown that TP does not afford better OS than TC regimens for definitive chemoradiation in patients with LA-ESCC [26]. However, higher rates of hematologic and gastrointestinal toxic effects were observed in the cisplatin group than in the carboplatin group.…”
Section: Discussionmentioning
confidence: 91%
“…Finally, another study evaluated platinum agents vs. fluoropyrimidine chemotherapy with taxane-based chemoradiation. Based on recently published results of this trial, there does not appear to be any difference in survival when comparing regimens offering the possibility of fluoropyrimidine- and taxane-based chemoradiation of patients with SCC [ 70 ]. A future trial may extend this to AC patients that are known to have a higher sensitivity to fluoropyrimidine-based regimens.…”
Section: Future Directions: Active Clinical Trialsmentioning
confidence: 99%